One step synthesis of ethyl levulinate biofuel by ethanolysis of renewable furfuryl alcohol over hierarchical zeolite catalyst - Nandiwale, Kakasaheb Y.; Pande, Ashwini M.; Bokade, Vijay V. (RSC Advances, 2015)
Ethanolysis of renewable furfuryl alcohol (FAL) to ethyl levulinate (EL) biofuel over various zeolites viz. H-ZSM-5 (microporous, medium pore), Hierarchical-HZ-5 (combination of micro-and meso pore), H-Beta (microporous, large pore) and Ultra Stable Y (USY, microporous, large pore) was studied in detail. To the best of our knowledge, probably for the first time, Hierarchical-HZ-5 synthesized by desilication post-treatment has been employed as a heterogeneous catalyst for ethanolysis of FAL. The synthesized catalysts were characterized by powder X-ray diffraction (PXRD), temperature programmed NH3 desorption (TPAD), Energy dispersive X-ray analysis (EDAX), etc. Response surface methodology (RSM) with Box-Behnken experimental design (BBD) was used to investigate the influence of three crucial process variables of ethanolysis such as ethanol to FAL molar ratio, percent catalyst loading and reaction temperature on EL yield. The optimization tool of design expert software was employed to obtain the optimum reaction parameters for FAL ethanolysis over Hierarchical-HZ-5 catalyst. Three intermediates of FAL ethanolysis reaction such as, ethoxymethylfuran (EMF), 4,5,5-triethoxypentan-2-one and diethyl ether (DEE) have been identified and quantified from the product mixture with the aid of Gas Chromatography-Mass Spectroscopy (GC-MS). Hierarchical-HZ-5 was found to be a potential catalyst for ethanolysis of FAL with 73% EL yield and 26% EMF yield at optimized process parameters.